Sales Data Visualization to Determine Business Insight Using Metabase in a Global Retail Company - Utomo, Fandy Setyo; Lubna, Zuhriyatul (Sistemasi: Jurnal Sistem Informasi, 2024)
In the era of dynamic business globalization, sales data analysis and visualization are key to strategic decision making. The application of Metabase as the main tool for visualization and analysis of sales data in the context of global retail companies, especially in the online sales sector. XYZ Company became the subject of research with complex challenges in managing extensive and diverse sales data. Metabase was adopted as a solution to deal with this complexity, enabling the company to gain deep insights into sales trends, consumer preferences, and hidden growth opportunities. Data visualization, through Metabase, plays a key role in transforming complex information into easy-to-understand visual representations, helping analysts and business stakeholders spot important patterns and trends. Research results reveal patterns of concurrent product purchases, providing opportunities to increase sales through promotions or product bundling. The identification of product categories that customers are interested in within a single transaction provides important insights for stock management and marketing strategies. Analysis of customer gender preferences opens up opportunities to direct more specific marketing strategies, focusing on the majority of a particular gender. The resulting recommendations include increased promotion or bundling of frequently purchased products together, as well as implementation of more focused marketing strategies based on product category preferences and customer gender. This article aims to contribute to the scientific literature on the practical application of data visualization in the context of sales analysis, with a focus on developing effective business decisions and marketing strategies.